PEMBUKTIAN SEDERHANA DALAM PERMOHONAN PEMBATALAN PERJANJIAN PERDAMAIAN OLEH KREDITUR YANG TIDAK MEMBERIKAN HAK SUARA DALAM RAPAT PERJANJIAN HOMOLOGASI (STUDI PUTUSAN NOMOR 49 K/PDT.SUS-PAILIT/2025) - Viely Yautarin Br Surbakti; Detania Sukarja; Robert (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the differing legal interpretations between the Commercial Court and the Supreme Court regarding the application of the principle of simple proof in cases involving a creditor’s petition to annul a settlement agreement where the creditor did not exercise their voting rights at the homologation meeting as addressed in Decision No. 49 K/Pdt.Sus-Pailit/2025. The research issues include the legal provisions on the annulment of a settlement agreement under the PKPU, the application of the principle of simple proof, and the judges’ reasoning in the decision. This study aims to analyze the applicable legal provisions, the application of the principle of simple proof, and the judges’ reasoning in the case. The research method used is a normative legal approach employing statutory analysis and case-based analysis through a literature review. The results indicate that a homologated settlement agreement is binding on all creditors, including those who did not exercise their right to vote. The right to file for annulment of the settlement remains possible if the debtor fails to fulfill the terms of the settlement in accordance with Article 170(1) of the UUK-PKPU. The application of the principle of simple proof should focus on the existence of two or more creditors and the existence of debts that have matured and are collectible, rather than on creditor participation in the homologation meeting. This study concludes that consistent application of the principle of simplified proof is necessary to ensure legal certainty and fair protection for all creditors.